Perspectives on Pentecostalism and Socio-Economic Transformation - Kirby, Benjamin (Exchange, 2014)
In this multiple book review I discuss four recent publications on the subject of Pentecostal Christianity, all of which address the public significance of contemporary Pentecostalism in different global contexts. I place a particular focus on the ways that these texts address the question of the capacity of Pentecostal discourses and practices to transform social and economic realities.